PARTAI ISLAM DI NEGARA MAYORITAS MUSLIM: STUDI PEMILU PERTAMA INDONESIA - Jamilludin Ali (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
The majority of Indonesian's populations are Moslems. The Islamic political elite saw the opportunity to take power by bringing the name of Islam to the political party. That are great opportunities because of the assumption that the majority of Moslems would vote for the Islamic party because Islamic party fighting for the benefit of Islam. However, history proves the Islamic party had never won in the general elections in Indonesia. Election of 1955 is regarded as the first democratic elections in Indonesia. It is fact. Although at that time the Moslems reach 90% of the total populations of Indonesia, the election results just put Islamic parties under nationalist party. The defeat of the Islamic party is caused by many things. Among these are the internal divisions in the Islamic party, is to promote party interests rather than Islam, and fierce resistance from nationalist and secular party.